Uticaj individualnog hirurškog volumena na rane postoperativne ishode posle resekcije rektuma zbog karcinoma - Aleksić, Zoran; Vulović, Maja; Milošević, Bojan; Cvetković, Aleksandar; Tomić, Dragan; Trkulja, Nebojša; Simatović, Milan; Stojković, Anđelka; Ivošević, Anita (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. Surgeon-specific experience as measured by procedure volume can have a significant impact on survival of patients with rectal cancer (RC). The aim of this study was to determine whether an individual surgeon-specific volume of procedure influences early postoperative outcomes as well as to determine the strength of different groups of annual surgeon volume (ASV), as a predictor of outcomes in patients after RC resection up to 30 days postoperatively. Methods. This retrospective observational single center study involved a cohort of 546 patients of both sexes, operated for a 10-year period due to RC. Patients were divided into three groups, according to the annual volume of RC procedures of a surgeon who operated them. Seven outcomes were analyzed: the incidence of colorectal anastomotic dehiscence (CRAD), operative time, intraoperative blood loss, hospital stay, in-hospital death, the status of the circumferential resection margin (CRM) and the total mesorectal excision (TME) with number of lymph nodes, as well as some risk factors (several independent, dependent and “confusing” variables) of importance for the outcome, to explain the difference. The strength of each group of surgeons and their effect on early outcome of treatment were determined. Results. The majority of surgeons (77.7%) belonged to the low and medium ASV, which performed a slightly higher number of surgeries (281) than the high volume group. The high-volume surgeon group was associated with significantly better results in four outcomes (CRAD, operating time, CRM, TME and number of lymph nodes). Conclusion. In our surgical institution, the high volume surgeon remains an important predictor of success of the RC surgery.